3D Computation of Lightning Leader Stepped Propagation Inside a Realistic Cloud - Dessante, Philippe (Comptes Rendus. Physique)
The simulation of lightning propagation is a complex problem studied for years. Here we propose to use the information from the electric potential created from a real cloud structure to study the propagation. The electric potential and field are calculated using a realistic thundercloud structure: the typical three layers cloud structure is constructed using a real cloud photograph. The different altitudes and separations of each layer are calculated from the luminosity of the picture and the space charge values are taken from data in the literature. A model of stepped leader propagation is proposed. It consists in finding by steps the path which maximises the potential difference taking into account the cloud and leader space charge. After each step, the electric potential is recalculated, and a new iteration gives a new direction. This framework permits us to analyse diverse cloud configurations. Only positive leaders from the base layer can reach the ground if the three layers are complete. Only negative lightning reaches the ground when the bottom positive layer is reduced (typical of the middle of a storm). Finally, when the two bottom layers are reduced in size (typical of the storm’s end), positive lightning from the upper positive layer can make its way into the cloud toward the ground. These simulated observations agree with the hypotheses made previously by Nag and Rakov.